A Review of Adverse Cutaneous Drug Reactions Resulting from the Use of Interferon and Ribavirin - Nisha Mistry; Jonathan Shapero; Richard I Crawford (Canadian Journal of Gastroenterology)
Drug-induced cutaneous eruptions are named among the most common side effects of many medications. Thus, cutaneous drug eruptions are a common cause of morbidity and mortality, especially in hospital settings. The present article reviews different presentations of drug-induced cutaneous eruptions, with a focus on eruptions reported secondary to the use of interferon and ribavirin. Presentations include injection site reactions, psoriasis, eczematous drug reactions, alopecia, sarcoidosis, lupus, fixed drug eruptions, pigmentary changes and lichenoid eruptions. Also reviewed are findings regarding life-threatening systemic drug reactions.